"One size fits all"? Convergence in international corporate social responsibility communication—A comparative study of CSR mission statements in the United States and India. Issue 3 (31st August 2017) - Fifka, Matthias S.; Kühn, Anna‐Lena; Stiglbauer, Markus
Abstract : So far, no study has investigated determinants that shape corporate social responsibility (CSR) communication in mission statements, as previous studies have focused on CSR reports and homepages. Our study, which is based on institutional theory, fills this gap. By conducting a directed content analysis of the statements of 200 listed companies in the United States and India, we examine the content conveyed with respect to 5 CSR dimensions, the 5 most prominent stakeholder groups, and additional components of CSR mission statements. Moreover, we examine whether Unted States and Indian companies' CSR communication varies according to their (a) home country, (b) industry affiliation, (c) degree of internationalization, (d) company size, (e) profitability, (f) founding year, (g) length of the CSR mission statement, and (h) compliance with the guidelines of the Global Reporting Initiative. Whereas the findings reveal that the companies' home country, degree of internationalization, and size have no considerable bearing on their CSR communication, we evidence that their communication can be explained by their industry affiliation, the profitability ratio return on assets, founding year, length of the statement, and compliance with the Global Reporting Initiative guidelines. Moreover, we explain the cross‐country conformity of CSR communication by a convergence towards global and universal CSR communication approaches.